Spatial distribution and long-term alterations of peripheral nerve lesions in schwannomatosis - Godel, Tim; Bäumer, Philipp; Farschtschi, Said; Hofstadler, Barbara; Heiland, Sabine; Gelderblom, Mathias; Bendszus, Martin; Mautner, Victor-Felix (Diagnostics, 2022)
Purpose: To examine the spatial distribution and long-term alterations of peripheral nerve lesions in patients with schwannomatosis by in vivo high-resolution magnetic resonance neurography (MRN). Methods: In this prospective study, the lumbosacral plexus as well as the right sciatic, tibial, and peroneal nerves were examined in 15 patients diagnosed with schwannomatosis by a standardized MRN protocol at 3 Tesla. Micro-, intermediate- and macrolesions were assessed according to their number, diameter and spatial distribution. Moreover, in nine patients, peripheral nerve lesions were compared to follow-up examinations after 39 to 71 months. Results: In comparison to intermediate and macrolesions, microlesions were the predominant lesion entity at the level of the proximal (p < 0.001), mid- (p < 0.001), and distal thigh (p < 0.01). Compared to the proximal calf level, the lesion number was increased at the proximal (p < 0.05), mid- (p < 0.01), and distal thigh level (p < 0.01), while between the different thigh levels, no differences in lesion numbers were found. In the follow-up examinations, the lesion number was unchanged for micro-, intermediate and macrolesions. The diameter of lesions in the follow-up examination was decreased for microlesions (p < 0.01), not different for intermediate lesions, and increased for macrolesions (p < 0.01). Conclusion: Microlesions represent the predominant type of peripheral nerve lesion in schwannomatosis and show a rather consistent distribution pattern in long-term follow-up. In contrast to the accumulation of nerve lesions, primarily in the distal nerve segments in NF2, the lesion numbers in schwannomatosis peak at the mid-thigh level. Towards more distal portions, the lesion number markedly decreases, which is considered as a general feature of other types of small fiber neuropathy.